An in vitro comparative study of bioglass and biologically derived hydroxyapatite with Bone Scintigraphy (BS) method - (:unkn) unknown (Trans Tech Publications Ltd, 2006)
Four rabbits received human derived HA to their left tibias. After 16 weeks bioglass was implanted to their right tibias. After other 16 weeks bone scintigraphies were taken with 99mTC-MDP. Three phase bone scan images showed no evidence of inflammation and superior vascularization rates at implantation sites. In this study, bioglass demonstrated higher uptake of 99mTc-MDP comparing to HA, suggesting a higher vascularization rate and better osseointegration.
Keywords: Bioglass; Bone Scintigraphy; Hydroxyapatite; Osseointegration